2021
DOI: 10.1002/slct.202103150
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Short Non‐Permeable Peptides to Increase Cellular Uptake and Cytostatic Activity of Their Conjugates

Abstract: Cell‐penetrating peptides (CPPs) are well‐known delivery vectors, oligoarginines are an important class of CPPs, which was modified to increase the cellular uptake and change the internalization mechanism. A minimum number of four Arg residues was used and tetrarginine sequence was modified by 4‐((4‐(dimethylamino)phenyl)azo)benzoic acid (Dabcyl) and Trp(s). The Dabcyl group was attached to the N‐terminus, while peptides were different in the number and position of Trp in their sequence. Their internalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…This has prompted the synthesis of Trp-containing, Arg-rich CPPs with improved internalization property [ 10 , 26 , 36 ]. We described that Dabcyl group increases the cellular uptake of hexa- and tetraarginine [ 32 ] and its effect may be further enhanced by Trp [ 33 ]. Two tetraarginine derivatives (Dabcyl-RRWRRK and Dabcyl-WRRRRK) were proven to be effective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has prompted the synthesis of Trp-containing, Arg-rich CPPs with improved internalization property [ 10 , 26 , 36 ]. We described that Dabcyl group increases the cellular uptake of hexa- and tetraarginine [ 32 ] and its effect may be further enhanced by Trp [ 33 ]. Two tetraarginine derivatives (Dabcyl-RRWRRK and Dabcyl-WRRRRK) were proven to be effective.…”
Section: Resultsmentioning
confidence: 99%
“…Another method to accurately measure the internalized peptide is the lysis of cells after accurate removal of extracellular and membrane-bound peptides, and subsequently measure the fluorescence intensity. Such a method can overcome bias related to the Dabcyl quenching of the fluorophore since the peptides are degraded by the cell-lysis released and added (trypsin) enzymes [ 32 , 33 ]. The internalization was quantified at 37 °C and 4 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent research, 4-(dimethylaminoazo) benzene-4-carboxylic acid (DABCYL) was used as a new kind of modification because of its structural simplicity, availability along with hydrophobicity, which could assist cell permeability. It has been demonstrated that utilizing the DABCYL group to modify arginine-rich CPPs effectively increases cellular uptake efficacy [ 104 , 105 , 106 ].…”
Section: Peptide Design Of the Arginine-rich Cppsmentioning
confidence: 99%
“…Although Dabcyl could enhance the internalization of tetraarginine, this effect was modest. For further improvement of cellular uptake, tryptophan was introduced into the Dabcyl-modified tetraarginine [ 156 ]. In spite of the fact that tryptophan insertion alone did not affect the internalization, the presence of Dabcyl highly increased the uptake.…”
Section: Modification Of Cppsmentioning
confidence: 99%